Mewujudkan Layanan Prima di Era Pandemi COVID-19 Melalui Pemanfaatan Fitur Booking Book - Badratun Nafis (Perpustakaan Nasional, 2022)
This study aims to find out how the level of satisfaction in the use and user feedback of the booking book feature service in the Syiah Kuala University Integrated Library Information System (UILIS) mobile library application during service restrictions as an effort to provide excellent service in the era of the COVID-19 pandemic. This research is quantitative because the data obtained are in the form of descriptive statistics and percentages. The method used is a survey, the sample in this study amounted to 65 people who were taken by random sampling. The data analysis technique used the descriptive analysis method, the data were analyzed by describing the picture and the results of the data that had been obtained. The results of the study indicate that the booking book feature is quite satisfactory for users, it can be seen from the level of utilization of the booking book feature. The development of the booking book feature has been to the lifestyle of today's society, which requires that the information sought can be found quickly and precisely. User feedback based on survey results shows that 75.69% of users agree that the booking book feature makes it very easy for them to get the books they need. Users also strongly agree that the booking feature is very useful and is a quick solution in getting the right collection service, with an average interpretation score of 82, 77%. The use of the USK Library's book booking feature is increasingly in demand to get books easily and save users' time. The results obtained are 72.61% of the booking book feature is quite satisfactory for users. The conclusion of this research is the USK Library still needs to improve the booking book feature service by making continuous improvements so that the utilization rate of the USK Library collection continues to increase.